Acessibilidade para a pessoa com cegueira em trilhas - Ramos, José Júlio Cordeiro (Universidade Federal de São Carlos, 2009)
The independence of blind people while in mobility, the object of this research, is one of areas that provide a high incidence of exclusion, since this is a limitation on a fundamental right of all citizens, which is the right of walking freely. The city of Florianópolis, place of this research and considered by the government organizations, a tourist destination offers many options of leisure such as beaches, mountains and forests. There are many trails in these places which are, commonly, used for walking or trekking. In general, these trails don t offer exclusive access to people with physical or visual impairment. For trekking , blind people need the assistance of a guide with normal vision. The propose of this research is to evaluate the accessibility for blind people on one of these trails, with their participation in this process through the application of modifications that allowed accessibility. The methodology involved some instruments used in previous research which were adapted for the conditions of blindness of the people with qualitative and early experimental approach. There are eleven blind people involved in the project, with skill in the use of normal guide, blind cane and Braille System. The principal instrument used in this research was a transit test on ecological trails, where we could observe the subjects involved. Could a blind person walk on trails, with independence? Is it possible these people walk beyond independence, with safety, too? And, the people in that walk are conscious of their space orientation and local attractive? The results have shown that with the utilization of a guide line, information plaques and sound signs, activated by a cane touch, that is, low worth materials, it is possible to offer an accessible trail for blind people.
Keywords: Deficiência visual; Acessibilidade; Trilha ecológica; Cegos; Educação especial; Deficiente visual; Special education; Visual impairment; Accessibility; Track; Blind people; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL